Change in expression of MGMT during maturation of human monocytes into dendritic cells - Briegert, Manuela; Enk, Alexander H.; Kaina, Bernd (DNA repair, 2007)
Dendritic cells (DCs) maturated from monocytes play an important role in the immune system, not only in defense against conventional infections but also in cancer rejection. Because of the central role of DCs in tumor host defense it is highly important that DCs as well as the progenitor cell population are protected during cancer therapy. Since most anticancer drugs target DNA, the DNA repair capacity is most importance for the response of DCs and their precursor cells. Here, we studied the expression of the DNA repair protein O 6-methylguanine-DNA methyltransferase (MGMT) in monocytes obtained from peripheral blood of healthy donors and DCs maturated from monocytes (moDCs). We show that MGMT is expressed at high level in monocytes, comparable to peripheral lymphocytes. The MGMT expression level declines, however, during DC maturation reaching the low level of CD34+ haematopoetic stem cells. Decline of MGMT was observed on activity, protein and RNA level. It is not related to MGMT promoter methylation, suggesting silencing of the MGMT gene in moDCs occurs by other means. Since maturation of monocytes into DCs is provoked by IL-4 and GM-CSF, the data indicate that MGMT is subject to cytokine-mediated regulation. Despite of the high MGMT level, monocytes were more sensitive to methylating agents (MNNG, temozolomide) and equally sensitive to the chloroethylating agent fotemustine than moDCs, undergoing apoptosis upon treatment. The data provide an example that high MGMT expression level does not necessarily implicate a higher level of resistance against O 6-alkylating agents.